Enhancing Village Management and Governance through Mobile Learning Initiatives - Mohd Taib, Nordiyana; Mat Amin, Rosemas Edayu; Hasan, Abdul Mutalib; Abd Rahman, Rahimah; Mohd Lokman, Anitawati (Journal of Technical Education and Training, 2024)
The Institute for Rural Advancement (INFRA), under the Ministry of Rural and Regional Development (KKDW), conducted a comprehensive outcome assessment of its mobile learning programme. This evaluation aligned with the TVET principle of practical, hands-on training, emphasizing real-world applications crucial for rural management. The study aimed to assess the programme’s impact on enhancing participants’ skills and knowledge in village management, including governance, financial management, and file system management. Quantitative survey was used to collect data from 219 trained participants. The results showed significant improvements in village management practices, with high effectiveness ratings across all dimensions. File management skills, demonstrated a strong acceptance of organized filing systems and improved administrative capacity. The findings also revealed notable improvements in village leadership, attributed to the programme’s focus on community engagement and practical field experiences. By aligning its mobile learning programme with TVET’s practical training pillar, INFRA has established itself as a leader in integrating TVET principles into rural management. This research offers valuable insights for policymakers and practitioners in designing effective rural development initiatives and enhancing village governance through targeted mobile learning programmes.